Binder for electric storage device, electrode for electric storage device, electric storage device, polymer composite, and method for manufacturing binder for electric storage device
The binder for power storage devices, comprising a polymer complex of a polyimide precursor and a cyclic molecule with multiple ether bonds, addresses the insufficient mechanical properties and charge/discharge cycle characteristics of existing binders, achieving enhanced performance in power storage devices.
Patent Information
- Application Number
- JP2024541755
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-31
- Filing Date
- 2024-03-22
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-03-22
AI Technical Summary
The existing binder for lithium-ion battery electrodes has insufficient mechanical properties and inadequate improvement in charge/discharge cycle characteristics.
A binder for power storage devices is developed, comprising a polymer complex formed by conjugating a polyimide precursor with a tetracarboxylic acid component and a diamine component, along with a cyclic molecule having multiple ether bonds, such as cyclodextrin, crown ether, or thiocrown ether.
The binder exhibits excellent mechanical properties and significantly improves the charge/discharge cycle characteristics of power storage devices, maintaining high breaking energy and flexibility.
Smart Images

Figure 0007648013000006 
Figure 0007648013000007 
Figure 0007648013000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a binder for an electricity storage device that has excellent mechanical properties and can improve charge / discharge cycle properties, an electrode for an electricity storage device obtained using the binder, an electricity storage device, and a method for producing the binder for an electricity storage device. The present invention also relates to a polymer composite having excellent mechanical properties. [Background technology]
[0002] Polyimides are excellent in heat resistance, solvent resistance (chemical resistance), mechanical properties, electrical properties, etc., and are therefore widely used in electrical and electronic equipment applications such as flexible wiring boards, tapes for TAB (Tape Automated Bonding), etc. For example, polyimides obtained from aromatic tetracarboxylic dianhydrides and aromatic diamines, particularly polyimides obtained from 3,3',4,4'-biphenyltetracarboxylic dianhydride and paraphenylenediamine, are preferably used.
[0003] Polyimide is also being considered for use as a binder for electrical storage devices, such as a binder for electrodes of lithium ion batteries. For example, Patent Document 1 discloses a binder for lithium ion battery electrodes, which contains a polyimide precursor, polyimide or polyamideimide, and a lithium salt, obtained by using a specific aromatic tetracarboxylic dianhydride and a specific diamine. Patent Document 1 also discloses that a negative electrode is obtained by blending a polyamic acid obtained by using an aromatic tetracarboxylic dianhydride and a diamine, and 12-crown-4 with a negative electrode active material. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-89437 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the binder for lithium ion battery electrodes disclosed in Patent Document 1 does not have sufficient mechanical properties, and is insufficient in improving the charge-discharge cycle characteristics. An object of the present invention is to provide a binder for an electricity storage device that has excellent mechanical properties and is capable of improving charge / discharge cycle characteristics. [Means for solving the problem]
[0006] In order to solve the above problems, the present inventors conducted extensive research and found that a binder containing a polymer composite in which a polyimide precursor and a cyclic molecule having a plurality of ether bonds are composited has high mechanical properties, particularly high breaking energy, and can improve charge-discharge cycle characteristics when applied to an electricity storage device, which led to the completion of the present invention.
[0007] That is, the present invention provides the following [1] to
[11] . [1] A binder for an electricity storage device, comprising a polymer composite obtained by combining a polyimide precursor containing a reaction product of a tetracarboxylic acid component and a diamine component and / or a polyimide obtained by imidizing a part or all of the polyimide precursor, and a cyclic molecule having a plurality of ether bonds.
[0008] [2] The binder for an electricity storage device according to [1], wherein the cyclic molecule is at least one selected from the group consisting of cyclodextrin, crown ether, and thiocrown ether.
[0009] [3] The binder for an electricity storage device according to [1] or [2], wherein the content of the cyclic molecules in the binder is 4 mol % or more and 25 mol % or less with respect to 100 mol % in total of amic acid groups and imide groups contained in the polyimide precursor and / or a polyimide obtained by imidizing a part or all of the polyimide precursor.
[0010] [4] The binder for an electricity storage device according to any one of [1] to [3], wherein the proportion of the alicyclic tetracarboxylic dianhydride in 100 mol % of the tetracarboxylic acid component is 35 mol % or more.
[0011] [5] The binder for an electricity storage device according to any one of [1] to [4], wherein the polymer composite is obtained by reacting the tetracarboxylic acid component with the diamine component in the presence of the cyclic molecule.
[0012] [6] A varnish comprising the binder for an electricity storage device according to any one of [1] to [5].
[0013] [7] An electrode for an electricity storage device, comprising the binder for an electricity storage device according to any one of [1] to [5] and an active material.
[0014] [8] The electrode for an electricity storage device according to [7], wherein the active material is a silicon-containing negative electrode active material.
[0015] [9] An electricity storage device comprising the electrode according to [7] or [8].
[0016]
[10] A method for producing a binder for an electricity storage device according to any one of [1] to [5], A method for producing a binder for an electrical storage device, comprising the step of reacting a tetracarboxylic acid component with a diamine component in the presence of a cyclic molecule having a plurality of ether bonds to obtain a polyimide precursor.
[0017]
[11] A polymer composite obtained by combining a polyimide precursor containing a reaction product of a tetracarboxylic acid component and a diamine component and / or a polyimide obtained by imidizing a part or all of the polyimide precursor with a cyclic molecule having a plurality of ether bonds, The polymer composite has an alicyclic tetracarboxylic dianhydride content of 35 mol % or more relative to 100 mol % of the tetracarboxylic acid component. Effect of the Invention
[0018] According to the present invention, it is possible to provide a binder for an electricity storage device that has excellent mechanical properties and can improve charge / discharge cycle properties, an electrode for an electricity storage device obtained using the binder, an electricity storage device, and a method for producing such a binder for an electricity storage device. The present invention can also provide a polymer composite having excellent mechanical properties. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 shows IR spectra of Example 1 and Comparative Example 2. [Diagram 2] FIG. 2 shows IR spectra of Example 2 and Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] <Binders for electricity storage devices> The binder for an electricity storage device of the present invention is a binder for use in an electricity storage device, which contains a polymer composite obtained by combining a polyimide precursor containing a reaction product of a tetracarboxylic acid component and a diamine component and / or a polyimide obtained by imidizing a part or all of the polyimide precursor, with a cyclic molecule having a plurality of ether bonds (including those in which a part or all of the ether bonds are thioether bonds; the same applies below). In the following, we will first explain the case where the polymer composite is formed by combining a polyimide precursor containing a reaction product of a tetracarboxylic acid component and a diamine component with a cyclic molecule having a plurality of ether bonds.
[0021] The binder for an electric storage device of the present invention may contain a polyimide precursor (hereinafter, also simply referred to as "polyimide precursor") containing a reaction product of a tetracarboxylic acid component and a diamine component, and a cyclic molecule (hereinafter, also simply referred to as "cyclic molecule") having a plurality of ether bonds, and may include a state in which at least a part of such polyimide precursor and at least a part of such cyclic molecule are complexed to form a polymer composite. That is, the binder for an electric storage device of the present invention may contain a polyimide precursor that is not complexed or a cyclic molecule that is not complexed, in addition to a state in which at least a part of the polyimide precursor and at least a part of the cyclic molecule are complexed to form a polymer composite. Furthermore, the binder for an electric storage device of the present invention may contain, in addition to a polyimide precursor, a polyimide in which a part or all of the polyimide precursor is imidized (that is, it may include a partially imidized polyimide in which a part of the amic acid structure constituting the polyimide precursor is imidized, or a completely imidized polyimide in which all of the amic acid structure constituting the polyimide precursor is imidized).
[0022] In the present invention, the polyimide precursor and the cyclic molecule being composited means that the polyimide precursor and the cyclic molecule are physically or chemically composited, and for example, refers to a state in which even when the binder for an electricity storage device of the present invention is heated for 5 minutes or more at a temperature 50°C or more higher than the boiling point of the cyclic molecule (i.e., (the boiling point of the cyclic molecule + 50)°C or more) (more specifically, when heated at 350°C for 5 minutes or more), 10% by weight or more of the cyclic molecules contained in the binder for an electricity storage device of the present invention remain without volatilizing, out of the total amount of cyclic molecules (100% by weight) contained in the binder for an electricity storage device of the present invention. For example, in the case of a binder containing 18-crown-6 (boiling point: 190° C.) as the cyclic molecule, when the binder is heated at a constant rate from room temperature to a temperature of 240° C. or higher for 5 minutes or more (more specifically, when heated at 350° C. for 5 minutes or more), 10% by weight or more of 18-crown-6 remains without volatilization out of 100% by weight of the total amount of 18-crown-6 contained in the binder for an electric storage device. When the binder for an electric storage device of the present invention is heated at a temperature higher than (boiling point of cyclic molecule+50)° C. for 5 minutes or more, the amount of cyclic molecules remaining without volatilization is preferably 15 to 100% by weight, more preferably 20 to 100% by weight, out of 100% by weight of the total amount of cyclic molecules contained in the binder for an electric storage device of the present invention. The above measurement may be performed in the form of a varnish in which the binder for an electric storage device of the present invention is dissolved or dispersed in a solvent. In the present invention, at least a part of the polyimide precursor and at least a part of the cyclic molecule may be composited by forming a rotaxane structure. In addition to the volatilized components, some cyclic molecules may be carbonized without being composited when heated at a temperature higher than (boiling point of cyclic molecule + 50) ° C. or more for 5 minutes or more. In this case, the proportion of the carbonized components when the cyclic molecule is heated alone may be calculated in advance, and the amount obtained by subtracting the amount of the carbonized components may be interpreted as the amount of the cyclic molecules remaining without being volatilized. For example, the proportion of the carbonized components in α-cyclodextrin is about 10% by weight, so this value may be subtracted.
[0023] In the present invention, the reason why the breaking energy is high and the charge-discharge cycle characteristics can be improved by compounding at least a part of the polyimide precursor with at least a part of the cyclic molecule is not necessarily clear; however, it is believed that the compounding of these makes it possible to increase strength while maintaining high flexibility, thereby effectively conforming to or mitigating the expansion and contraction caused by charging and discharging of the active material used in the electricity storage device.
[0024] The polyimide precursor is obtained by reacting a tetracarboxylic acid component with a diamine component to form an amide bond (-CONH-). The polyimide precursor preferably contains a repeating unit represented by the following formula (1), more preferably 50 mol % or more, even more preferably 75 mol % or more, and even more preferably 90 mol % or more. [ka] In the above formula (1), A is one or more tetravalent groups obtained by removing a carboxyl group from an aromatic tetracarboxylic acid or an aliphatic tetracarboxylic acid, and B is one or more divalent groups obtained by removing an amino group from an aromatic diamine or an aliphatic diamine.
[0025] Examples of the tetracarboxylic acid component include aromatic tetracarboxylic acid dianhydrides and aliphatic tetracarboxylic acid dianhydrides, etc. These can be used alone or in combination of two or more kinds.
[0026] As the aromatic tetracarboxylic dianhydride, a tetracarboxylic dianhydride having an aromatic ring can be suitably used. Specific examples of the aromatic tetracarboxylic dianhydride include 3,3',4,4'-biphenyltetracarboxylic dianhydride (s-BPDA), pyromellitic dianhydride (hereinafter also referred to as "PMDA"), 2,3,3',4'-biphenyltetracarboxylic dianhydride, 4,4'-oxydiphthalic dianhydride, diphenylsulfone-3,4,3',4'-tetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)sulfonate, and bis(3,4-dicarboxyphenyl)sulfonate. Sulfide dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride (also known as 4,4'-(hexafluoroisopropylidene)diphthalic anhydride), 2,3,3',4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3 ,4-dicarboxyphenyl)propane dianhydride, p-phenylene bis(trimellitic acid monoester acid anhydride), p-biphenylene bis(trimellitic acid monoester acid anhydride), m-terphenyl-3,4,3',4'-tetracarboxylic acid dianhydride, p-terphenyl-3,4,3',4'-tetracarboxylic acid dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, 2,2-bis[(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, 2,3,6,7-naphthalene tetracarboxylic acid dianhydride, 1,4,5,8-naphthalene tetracarboxylic acid dianhydride, 4,4'-(2,2-hexafluoroisopropylidene)diphthalic acid dianhydride, and the like. These may be used alone or in combination of two or more.
[0027] As the aliphatic tetracarboxylic dianhydride, an alicyclic tetracarboxylic dianhydride (a tetracarboxylic dianhydride having an alicyclic structure and no aromatic ring) can be suitably used. Specific examples of the alicyclic tetracarboxylic dianhydride include (1R,2S,4S,5R)-cyclohexanetetracarboxylic dianhydride (hereinafter also referred to as "H''-PMDA"), (1S,2R,4S,5R)-cyclohexanetetracarboxylic dianhydride, (1S,2S,4R,5R)-cyclohexanetetracarboxylic dianhydride (hereinafter also referred to as "H'-PMDA"), bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic dianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride (hereinafter also referred to as "BTA"), 4-(2,5-dioxotetrahydrofuran), and 1,2,3,5,6-dioxotetrahydrofuran. tetrahydrofuran-3-yl)-tetralin-1,2-dicarboxylic acid dianhydride, tetrahydrofuran-2,3,4,5-tetracarboxylic acid dianhydride, bicyclo-3,3',4,4'-tetracarboxylic acid dianhydride, 1,2,3,4-cyclopentane tetracarboxylic acid dianhydride, 1,2,3,4-cyclobutane tetracarboxylic acid dianhydride (hereinafter also referred to as "CBDA"), 1,3-dimethyl-1,2,3,4-cyclobutane tetracarboxylic acid dianhydride, 1,4-dimethyl-1,2,3,4-cyclobutane tetracarboxylic acid dianhydride, 1,2,3,4-cyclohexane tetracarboxylic acid dianhydride, pentacyclo[8.2.1.1 4,7 .0 2,9 .0 3,8 ]tetradecane-5,6,11,12-tetracarboxylic dianhydride, 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic dianhydride, cyclohex-1-ene-2,3,5,6-tetracarboxylic dianhydride, bicyclo[2.2.1]heptane-2,3,5,6-tetracarboxylic dianhydride, etc. These may be used alone or in combination of two or more.
[0028] In the present invention, from the viewpoint of further increasing the breaking energy and further improving the effect of charge / discharge characteristics such as charge / discharge cycle characteristics and Coulombic efficiency, it is preferable to use at least an alicyclic tetracarboxylic acid dianhydride as the tetracarboxylic acid component, and the proportion of the alicyclic tetracarboxylic acid dianhydride in 100 mol % of the tetracarboxylic acid component is preferably 35 mol % or more, more preferably 50 mol % or more, even more preferably 70 mol % or more, still more preferably 90 mol % or more, and particularly preferably 100 mol % of the alicyclic tetracarboxylic acid dianhydride.
[0029] From the viewpoint of enhancing the effect of improving charge-discharge cycle characteristics and charge-discharge characteristics such as coulombic efficiency, preferred alicyclic tetracarboxylic dianhydrides are H″-PMDA, CBDA, norbornane-2-spiro-α-cyclopentanone-α'-spiro-2″-norbornane-5,5”,6,6”-tetracarboxylic dianhydride (CpODA), [1,1′-bi(cyclohexane)]-3,3′,4,4′-tetracarboxylic acid (H-BPDA), H″-PMDA, and BTA, with H″-PMDA and CBDA being more preferred because they provide a greater effect of improving charge-discharge cycle characteristics. Preferred aromatic tetracarboxylic dianhydrides are s-BPDA and PMDA, with PMDA being more preferred because they provide a greater effect of improving charge-discharge cycle characteristics.
[0030] Examples of diamine compounds as the diamine component include 4,4'-diaminodiphenyl ether (hereinafter also referred to as "ODA"), 2,2'-dimethylbenzidine, 4,4'-diaminodiphenylmethane, 4,4'-diamino-1,2-diphenylethane, p-phenylenediamine (PPD), m-phenylenediamine, 2,4-diaminotoluene, 1,3-bis(4-aminophenoxy)benzene (hereinafter also referred to as "TPE-R"), 1,4-bis(4-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy) aromatic diamines having an aromatic group, such as 4,4'-diaminobenzanilide (hereinafter also referred to as "DABAN"), m-xylylenediamine, p-xylylenediamine, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-methylenebis(2,6-xylidine), α,α'-bis(4-aminophenyl)-1,4-diisopropylbenzene, 2,2'-dimethyl-4,4'-aminobiphenyl, 3,3'-dimethyl-4,4'-aminobiphenyl, 2,2'-ethylenedianiline, and 4,4'-diaminobenzanilide (hereinafter also referred to as "DABAN");1,4-diaminocyclohexane, 1,4-diamino-2-methylcyclohexane, 1,4-diamino-2-ethylcyclohexane, 1,4-diamino-2-n-propylcyclohexane, 1,4-diamino-2-isopropylcyclohexane, 1,4-diamino-2-n-butylcyclohexane, 1,4-diamino-2-isobutylcyclohexane, 1,4-diamino-2-sec-butylcyclohexane, 1,4-diamino-2-tert-butylcyclohexane, 1,2-diaminocyclohexane, 1,3-diaminocyclobutane, 1,4-bis(aminomethyl)cyclohexane, 1,3-bis(aminomethyl)cyclohexane alicyclic diamines having an alicyclic structure, such as bis(aminocyclohexyl)cyclohexane, diaminobicycloheptane, diaminomethylbicycloheptane, diaminooxybicycloheptane, diaminomethyloxybicycloheptane, isophoronediamine, diaminotricyclodecane, diaminomethyltricyclodecane, bis(aminocyclohexyl)methane, bis(aminocyclohexyl)isopropylidene, 6,6'-bis(3-aminophenoxy)-3,3,3',3'-tetramethyl-1,1'-spirobiindane, and 6,6'-bis(4-aminophenoxy)-3,3,3',3'-tetramethyl-1,1'-spirobiindane;2,2'-Bis(trifluoromethyl)-4,4'-diaminobiphenyl, 2,2'-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,3,5,6-tetrafluoro-1,4-diaminobenzene, 2,4,5,6-tetrafluoro-1,3-diaminobenzene, 2,3,5,6-tetrafluoro-1,4-benzene(dimethanamine), 2,2'-difluoro-(1,1'-biphenyl)-4,4'-diamine, 2,2',6,6'-tetrafluoro-(1,1'-biphenyl)-4,4'-diamine, 4,4'-diaminooctafluorobiphenyl, 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4'-oxybis(2,3,5 ,6-tetrafluoroaniline), 3,3'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 4,4'-diamino-2,2'-bis(trifluoromethyl)diphenyl ether, 1,4-bis[4-amino-2-(trifluoromethyl)phenoxy]benzene, 2,2-bis[4-[4-amino-2-(trifluoromethyl)phenoxy]hexafluoropropane, 3,5-diaminobenzene trifluoride, 4,4-diamino-2-(trifluoromethyl)diphenyl ether, and other fluorine-containing diamines; ester bond-containing diamines, such as 4-aminobenzoic acid 4-aminophenyl, terephthalic acid bis(4-aminophenyl), and the like. These may be used alone or in combination of two or more.;
[0031] From the viewpoint of enhancing the effect of improving charge-discharge cycle characteristics, coulombic efficiency, and other charge-discharge characteristics, the diamine compound as the diamine component is preferably ODA, TPE-R, or DABAN, and more preferably contains ODA alone or in combination with ODA and TPE-R or DABAN.
[0032] The cyclic molecule is not particularly limited as long as it has a plurality of ether bonds and a cyclic molecular structure, but from the viewpoint of increasing the breaking energy and from the viewpoint of increasing the effect of improving the charge-discharge cycle characteristics, it is preferably at least one selected from cyclodextrin, crown ether, and thiocrown ether, more preferably cyclodextrin and crown ether, and even more preferably crown ether. Examples of cyclodextrin include α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin, and examples of crown ether include 12-crown-4, 15-crown-5, 18-crown-6, dibenzo-18-crown-6, and diaza-18-crown-6, and among these, 18-crown-6 is preferred from the viewpoint of its high action and effect.
[0033] The content of the cyclic molecules in the binder for an electrical storage device of the present invention is preferably 4 mol% or more and 25 mol% or less, more preferably 10 mol% or more and more preferably 20 mol% or less, based on 100 mol% of the total of the amic acid groups and imide groups contained in the polyimide precursor and / or the polyimide obtained by imidizing a part or all of the polyimide precursor. The content of the cyclic molecules in the binder for an electrical storage device of the present invention in terms of weight, based on 100 mol% of the total of the polyimide precursor and the cyclic molecules, is preferably 5 mol% or more and 25 mol% or less, more preferably 10 mol% or more and more preferably 20 mol% or less.
[0034] <Method for producing binder for power storage device> The binder for an electricity storage device of the present invention includes a step of reacting a tetracarboxylic acid component with a diamine component in the presence of a cyclic molecule to form an amide bond, thereby forming a polyimide precursor. According to the present invention, by allowing cyclic molecules to be present when a tetracarboxylic acid component and a diamine component are reacted, at least a part of the polyimide precursor and at least a part of the cyclic molecule can be complexed, and thus a polymer composite in which they are complexed can be obtained.
[0035] The method of reacting the tetracarboxylic acid component and the diamine component in the presence of the cyclic molecule is not particularly limited. For example, the tetracarboxylic acid component and the diamine component in approximately equimolar amounts are reacted in a solvent in the presence of the cyclic molecule at a relatively low temperature of 100° C. or less, preferably 80° C. or less, so that the imidization reaction does not proceed or proceeds too much, to obtain a state in which the polymer composite is dissolved in the solvent, that is, in the state of a polymer composite solution. The polymer composite solution thus obtained may contain, in addition to the polyamic acid as the polyimide precursor, a polyimide formed by the imidization reaction proceeding. In this case, the polyimide may be one in which a part of the amic acid structure of the polyimide precursor is imidized, or may be one in which the entirety is imidized. In this case, in addition to at least a part of the polyimide precursor, at least a part of the polyimide may also be in a state of being complexed with the cyclic molecule.
[0036] The polymerization temperature when obtaining the polyimide precursor is preferably 25°C or higher and 100°C or lower, more preferably 40°C or higher and 80°C or lower, and even more preferably 50°C or higher and 80°C or lower. The polymerization time is preferably 0.1 hours or higher and 24 hours or lower, more preferably 2 hours or higher and 12 hours or lower. By setting the polymerization temperature and polymerization time within the above ranges, a high molecular weight polyimide precursor can be easily obtained with high production efficiency. The polymerization can be carried out in an air atmosphere, but is usually preferably carried out in an inert gas atmosphere, preferably a nitrogen gas atmosphere. The molar ratio of the tetracarboxylic acid component and the diamine component, which are approximately equimolar, is specifically 0.90 or higher and 1.10 or lower, preferably 0.95 or higher and 1.05 or lower, more preferably more than 0.98 and 1.04 or lower, and even more preferably more than 0.98 and 1.03 or lower. In this specification, "almost equimolar" means that the molar ratio is in the range of more than 0.99 to 1.01, and "equimolar" means the significant figures of a molar ratio of 1.00.
[0037] When reacting a tetracarboxylic acid component with a diamine component in the presence of a cyclic molecule, a method can be preferably adopted in which the cyclic molecule and the diamine component are usually added to a polymerization apparatus filled with a solvent, and the tetracarboxylic acid component is added after confirming that the cyclic molecule and the diamine component have been dissolved.
[0038] The solvent used in reacting the tetracarboxylic acid component with the diamine component in the presence of the cyclic molecule may be any solvent capable of polymerizing the polyimide precursor and dissolving the polyimide precursor, and may be either an aqueous solvent or an organic solvent. The solvent may be a mixture of two or more types, and a mixed solvent of two or more types of organic solvents or a mixed solvent of water and one or more types of organic solvents may also be used. The organic solvent is not particularly limited, but examples thereof include N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, N-methylcaprolactam, hexamethylphosphorotriamide, 1,2-dimethoxyethane, bis(2-methoxyethyl)ether, 1,2-bis(2-methoxyethoxy)ethane, tetrahydrofuran, bis[2-(2-methoxyethoxy)ethyl]ether, 1,4-dioxane, dimethyl sulfoxide, dimethyl sulfone, diphenyl ether, sulfolane, diphenyl sulfone, tetramethylurea, anisole, m-cresol, phenol, and γ-butyrolactone.
[0039] The binder for the electric storage device of the present invention can be produced by removing the solvent used in the polymerization from the polymer composite solution obtained as described above. The method for removing the solvent is not particularly limited, and includes a method of drying the solvent. The binder for the electric storage device of the present invention may be dissolved or dispersed in a solvent to form a varnish containing the binder for the electric storage device. As the solvent constituting the varnish for the electric storage device binder, the solvent used in polymerizing the polyimide precursor in the presence of the cyclic molecule may be used as it is as the solvent for the varnish for the electric storage device binder, or a solvent different from the solvent used in the polymerization may be used. When a solvent different from the solvent used in the polymerization is used, the solvent used in the polymerization may be removed by drying or the like, and then dissolved or dispersed in another solvent, or may be replaced with another solvent.
[0040] The solids concentration of the polymer composite in the varnish of the binder for electricity storage devices is not particularly limited, but is preferably 5 mass % or more and 45 mass % or less, more preferably 5 mass % or more and 40 mass % or less, and even more preferably more than 10 mass % and 30 mass % or less, based on the total amount of the polymer composite and the solvent.
[0041] If necessary, the varnish of the binder for the electricity storage device may contain known additives, such as an amine compound, an additive that promotes an imidization reaction, such as a dehydrating agent, an organic phosphorus-containing compound, the above-mentioned filler, a surfactant, a silane coupling agent, and a leveling agent.
[0042] Examples of the amine compound include substituted or unsubstituted nitrogen-containing heterocyclic compounds, N-oxide compounds of the nitrogen-containing heterocyclic compounds, substituted or unsubstituted amino acid compounds, aromatic hydrocarbon compounds or aromatic heterocyclic compounds having a hydroxyl group. Specific examples of the imidization catalyst include imidazole derivatives such as 1,2-dimethylimidazole, N-methylimidazole, 2-methylimidazole, 2-ethyl-4-methylimidazole, 5-methylbenzimidazole, and N-benzyl-2-methylimidazole, and substituted pyridine derivatives such as isoquinoline, 3,5-dimethylpyridine, 3,4-dimethylpyridine, 2,5-dimethylpyridine, 2,4-dimethylpyridine, and 4-n-propylpyridine. The amount of the imidization catalyst used is preferably 0.01 equivalent or more and 2 equivalents or less, more preferably 0.02 equivalent or more, and more preferably 1 equivalent or less, relative to the amic acid unit of the polyamide precursor. Use of an imidization catalyst may improve the physical properties of the resulting binder for an electricity storage device, in particular the elongation and edge tear resistance.
[0043] Other amine compounds include aliphatic tertiary amines such as trimethylamine and triethylenediamine, aromatic tertiary amines such as dimethylaniline, and heterocyclic tertiary amines such as isoquinoline, pyridine, α-picoline, and β-picoline, and can be added as necessary.
[0044] Examples of the dehydrating agent include aliphatic carboxylic acid anhydrides such as acetic anhydride, propionic anhydride, and butyric anhydride, and aromatic carboxylic acid anhydrides such as benzoic anhydride.
[0045] Examples of the organic phosphorus-containing compound include phosphates such as monocaproyl phosphate, monooctyl phosphate, monolauryl phosphate, monomyristyl phosphate, monocetyl phosphate, monostearyl phosphate, monophosphate of triethylene glycol monotridecyl ether, monophosphate of tetraethylene glycol monolauryl ether, monophosphate of diethylene glycol monostearyl ether, dicaproyl phosphate, dioctyl phosphate, dicapryl phosphate, dilauryl phosphate, dimyristyl phosphate, dicetyl phosphate, distearyl phosphate, diphosphate of tetraethylene glycol mononeopentyl ether, diphosphate of triethylene glycol monotridecyl ether, diphosphate of tetraethylene glycol monolauryl ether, and diphosphate of diethylene glycol monostearyl ether, as well as amine salts of these phosphates. Examples of the amine include ammonia, monomethylamine, monoethylamine, monopropylamine, monobutylamine, dimethylamine, diethylamine, dipropylamine, dibutylamine, trimethylamine, triethylamine, tripropylamine, tributylamine, monoethanolamine, diethanolamine, and triethanolamine.
[0046] In the present invention, the polyimide precursor contained in the polymer composite constituting the binder for the electric storage device may be imidized to form a polymer composite in which a polyimide obtained by imidizing a polyimide precursor containing a reaction product of a tetracarboxylic acid component and a diamine component is composited with a cyclic molecule having a plurality of ether bonds. In this case, it is sufficient that at least a part of the polyimide and at least a part of the cyclic molecule are composited to form a polymer composite. That is, the binder for the electric storage device of the present invention may contain uncomplexed polyimide or uncomplexed cyclic molecule in addition to a polymer composite in which at least a part of the polyimide and at least a part of the cyclic molecule are composited.
[0047] The polyimide preferably contains a polyimide containing a repeating unit represented by the following formula (2) as a main component (50 mol % or more), more preferably 75 mol % or more, and even more preferably 90 mol % or more. That is, the polyimide may be a partially imidized polyimide in which a part of the amic acid structure contained in the polyimide precursor is imidized, or a completely imidized polyimide in which all of the amic acid structures contained in the polyimide precursor are imidized, or may be a mixture of these. [ka] In the above formula (2), X1 is one or more tetravalent groups obtained by removing a carboxyl group from an aromatic or aliphatic tetracarboxylic acid, and Y1 is one or more divalent groups obtained by removing an amino group from an aromatic or aliphatic diamine.
[0048] In the present invention, the polyimide and the cyclic molecules are composited, so long as the polyimide and the cyclic molecules are physically or chemically composited. For example, when the binder for an electric storage device of the present invention is heated at a temperature 50° C. or more higher than the boiling point of the cyclic molecules (i.e., (boiling point of the cyclic molecules +50)° C. or more) for 5 minutes or more (more specifically, when heated at 350° C. for 5 minutes or more), 10% by weight or more of the cyclic molecules remain without volatilizing, based on 100% by weight of the total amount of the cyclic molecules contained in the binder for an electric storage device of the present invention. When the binder for an electric storage device of the present invention is heated at a temperature (boiling point of the cyclic molecules +50)° C. or more higher for 5 minutes or more, the amount of the cyclic molecules remaining without volatilizing is preferably 15 to 100% by weight, more preferably 20 to 100% by weight, based on 100% by weight of the total amount of the cyclic molecules contained in the binder for an electric storage device of the present invention. The above measurement may be performed in the form of a varnish containing the binder for an electric storage device of the present invention. In the present invention, at least a part of the polyimide and at least a part of the cyclic molecule may be combined to form a rotaxane structure.
[0049] The method for imidizing the polyimide precursor is not particularly limited, and examples thereof include a method for chemically imidizing and / or thermally imidizing a polymer composite containing the polyimide precursor and the cyclic molecule. Chemical imidization and / or thermal imidization may be performed in the state of a solution of the polymer composite containing the polyimide precursor and the cyclic molecule, or may be performed after the solvent has been removed by drying or the like.
[0050] In the present invention, chemical imidization / thermal imidization can be performed by heat treatment. To explain by taking thermal imidization as an example, the maximum heating temperature in the heat treatment is usually 150°C or higher, preferably 200°C or higher, more preferably 250°C or higher, and even more preferably 350°C or higher. The upper limit of the heat treatment temperature may be any temperature at which the properties do not deteriorate, and is preferably 450°C or lower, more preferably 430°C or lower, and even more preferably 400°C or lower. The heat treatment can be performed in an air atmosphere, but is usually preferably performed in an inert gas atmosphere, preferably nitrogen gas atmosphere. Chemical imidization can be performed under milder heat treatment conditions than thermal imidization, depending on the type of additive such as a chemical imidization catalyst. For example, heat treatment may be performed in a temperature range of usually 100°C or higher, preferably 120°C or higher, more preferably 150°C or higher, and even more preferably 200°C or higher, and usually 360°C or lower, preferably 300°C or lower, more preferably 250°C or lower, and even more preferably 220°C or lower.
[0051] Heat treatment for chemical imidization / or thermal imidization may be carried out stepwise. For example, a first heat treatment is preferably carried out at a relatively low temperature of 100°C or more and 170°C or less for 0.5 minutes or more and 30 minutes or less, then a second heat treatment is preferably carried out at a temperature of more than 170°C and less than 220°C for 0.5 minutes or more and 30 minutes or less, and then a third heat treatment is preferably carried out at a high temperature of more than 220°C and less than 350°C for 0.5 minutes or more and 30 minutes or less, and a fourth high-temperature heat treatment can be carried out from 350°C or more to the maximum heating temperature. It is preferable to carry out the heat treatment continuously. For example, it is preferable to carry out the heat treatment from a relatively low temperature of 100°C or more and 170°C or less to the maximum heating temperature. There is no particular restriction on the temperature rise rate, but it is preferably 1°C / min or more and 30°C / min or less, and particularly preferably 2°C / min or more and 20°C / min or less. If it is within the above range, it is preferable because foaming due to a sudden temperature rise can be suppressed.
[0052] <Electrodes for electricity storage devices> The electrode for the power storage device of the present invention contains the binder for the power storage device of the present invention described above and an active material. The active material may be either a negative electrode active material or a positive electrode active material. That is, the electrode for the power storage device of the present invention may be a negative electrode or a positive electrode.
[0053] When the electrode for the power storage device of the present invention is a negative electrode, examples of the negative electrode active material include, particularly as a negative electrode active material for a lithium secondary battery, lithium metal, a lithium alloy, a carbon material capable of occluding and releasing lithium [graphitizable carbon, non-graphitizable carbon with an interplanar spacing of the (002) plane of 0.37 nm or more, graphite with an interplanar spacing of the (002) plane of 0.34 nm or less, etc.], tin (single substance), tin compounds, silicon (single substance), silicon compounds, Li4Ti5O 12 and lithium titanate compounds such as the like. These can be used alone or in combination of two or more. As the negative electrode active material, a silicon-containing negative electrode active material such as silicon (single substance) or a silicon compound is preferable because the effect of improving the charge-discharge cycle characteristics by using the binder for the power storage device of the present invention is great. A silicon-containing negative electrode active material such as silicon (single substance) or a silicon compound has an extremely large theoretical capacity compared to graphite, while having a relatively large volume expansion rate of the negative electrode active material itself during charging. According to the binder for the power storage device of the present invention, since the fracture energy is high, such volume expansion can be appropriately relaxed, and thereby, it is considered that the charge-discharge cycle characteristics can be more appropriately improved.
[0054] The silicon-containing negative electrode active material is not particularly limited, and examples thereof include silicon (single substance), silicon compounds, partially substituted silicon, partially substituted silicon compounds, solid solutions of silicon compounds, and the like. Specific examples of the silicon compound include silicon oxides represented by SiO x (0.05 < x < 1.95), silicon carbides represented by SiC y (0 < y < 1), and silicon nitrides represented by SiN zSilicon nitride represented by (0 < z < 4 / 3), silicon alloys such as alloys of silicon and a different element M1, etc. are preferably cited. In the silicon alloy, as the different element M1, at least one element selected from the group consisting of Fe, Co, Sb, Bi, Pb, Ni, Cu, Zn, Ge, In, Sn, and Ti is preferably cited.
[0055] Further, the silicon partial substitute is a compound in which a part of the silicon contained in silicon (simple substance) and silicon compounds is substituted with a different element M2. Specific examples of the different element M2 include, for example, B, Mg, Ni, Ti, Mo, Co, Ca, Cr, Cu, Fe, Mn, Nb, Ta, V, W, Zn, C, N, and Sn, etc. Among these silicon-containing negative electrode active materials, silicon (simple substance), silicon oxide, or silicon alloy is preferable, and silicon (simple substance) or silicon oxide is more preferable.
[0056] When the electrode for the power storage device of the present invention is a negative electrode, in addition to the negative electrode active material, a conductive material may be contained. The conductive material is not particularly limited as long as it is an electron conductive material that does not cause a chemical change, but it is preferable to use metal powders such as copper, nickel, titanium, or aluminum, carbon materials, etc. As the carbon material, one or more carbon blacks selected from natural graphite (such as flaky graphite), graphite such as artificial graphite, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, fibrous carbon powders such as carbon nanotubes and carbon fibers, etc. are preferably cited.
[0057] When the electrode for the power storage device of the present invention is a positive electrode, as the positive electrode active material, particularly as a positive electrode active material for a lithium secondary battery, a composite metal oxide with lithium containing one or more selected from cobalt, manganese, and nickel is cited. As such a lithium composite metal oxide, for example, LiCoO2, LiMn2O4, LiNiO2, LiCo 1-x Ni x O2 (0.01 < x < 1), LiCo 1 / 3 Ni 1 / 3 Mn1 / 3 O2, LiNi 1 / 2 Mn 3 / 2 O4, LiCo 0.98 Mg 0.02 LiCoO2 and LiMn2O4, LiCoO2 and LiNiO2, LiMn2O4 and LiNiO2, etc. may also be used in combination.
[0058] When the electrode for the power storage device of the present invention is a positive electrode, it may contain a conductive material in addition to the positive electrode active material. The conductive material is not particularly limited as long as it is an electron conductive material that does not undergo chemical changes, and suitable examples include graphite such as natural graphite (e.g., flake graphite) and artificial graphite, one or more types of carbon black selected from acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, and fibrous carbon powder such as carbon nanotubes and carbon fibers.
[0059] The electrode for the electric storage device of the present invention can be manufactured by mixing the above-mentioned electric storage device binder of the present invention, the negative electrode active material or the positive electrode active material, and the conductive material used as necessary to obtain an electrode mixture, and forming it into a sheet shape or the like. When mixing the electric storage device binder of the present invention, the negative electrode active material or the positive electrode active material, and the conductive material used as necessary, a solvent may be used to form a slurry. In addition, in this case, when a binder in the form of a varnish is used as the electric storage device binder of the present invention, the negative electrode active material or the positive electrode active material and the conductive material used as necessary may be mixed in the form of a varnish to form a slurry, and in this case, a solvent may be further added to adjust the solid content concentration.
[0060] The electrode for the power storage device of the present invention can be formed into a sheet shape by, for example, casting or applying a slurry containing the binder for the power storage device of the present invention, a negative electrode active material or a positive electrode active material, and a conductive material used as necessary onto a conductive current collector such as aluminum foil or copper foil, heating to remove the solvent, and applying pressure as necessary to form an active material layer on the current collector. When a binder for the power storage device of the present invention containing a polymer complex formed by compounding a polyimide precursor and a cyclic molecule is used, the imidization reaction may be advanced by heating when forming an active material layer on the current collector, and the polyimide precursor may be converted into a polyimide.
[0061] The thickness of the active material layer of the present invention may be appropriately determined depending on the application and the desired capacity. Although not limited, it is preferable to use it in the range of 0.1 μm or more and 500 μm or less. More preferably, it is 1 μm or more, even more preferably, 10 μm or more, even more preferably, 20 μm or more, more preferably, 300 μm or less, even more preferably, 100 μm or less, and even more preferably, 50 μm or less.
[0062] <Electricity storage device> The electricity storage device of the present invention includes the above-mentioned electrode for the electricity storage device of the present invention. The electricity storage device includes electricity storage devices such as lithium batteries, electric double layer capacitors, and lithium ion capacitors. Among these, lithium batteries using a lithium salt as the electrolyte salt are preferred, and lithium secondary batteries are suitable.
[0063] The lithium secondary battery includes a positive electrode, a negative electrode, a non-aqueous electrolyte, a separator, and the like, and may be configured as a known configuration required for a lithium secondary battery. In the present invention, the above-mentioned electrode for the power storage device of the present invention is used as the positive electrode and / or the negative electrode. The lithium secondary battery may be a lithium polymer battery using a gel electrolyte as the electrolyte, or an all-solid-state battery using an inorganic solid electrolyte such as an oxide or sulfide system.
[0064] The non-aqueous electrolyte is a non-aqueous solvent having an electrolyte salt dissolved therein. There are no particular limitations on the type of non-aqueous electrolyte, and various types can be used.
[0065] The electrolyte salt used is one that dissolves in a non-aqueous electrolyte, and examples of such electrolyte salts include inorganic lithium salts such as LiPF6, LiBF4, LiPO2F2, LiN(SO2F)2, and LiClO4; lithium salts containing a chain-like fluorinated alkyl group such as LiN(SO2CF3)2, LiN(SO2C2F5)2, LiCF3SO3, LiC(SO2CF3)3, LiPF4(CF3)2, LiPF3(C2F5)3, LiPF3(CF3)3, LiPF3(iso-C3F7)3, and LiPF5(iso-C3F7); lithium salts containing a cyclic fluorinated alkylene chain such as (CF2)2(SO2)2NLi and (CF2)3(SO2)2NLi; and lithium salts having an oxalate complex as the anion, such as lithium bis[oxalate-O,O']borate and lithium difluoro[oxalate-O,O']borate.
[0066] The concentration of all of these electrolyte salts dissolved in the non-aqueous solvent is preferably 0.3 M or more, more preferably 0.5 M or more, and even more preferably 0.7 M or more. The upper limit is preferably 2.5 M or less, more preferably 2.0 M or less, and even more preferably 1.5 M or less.
[0067] Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, chain esters, ethers, amides, phosphate esters, sulfones, lactones, nitriles, S=O bond-containing compounds, etc., and preferably contain cyclic carbonates. The term "chain ester" is used as a concept including chain carbonates and chain carboxylate esters.
[0068] Examples of the cyclic carbonate include one or more selected from ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 4-fluoro-1,3-dioxolan-2-one (FEC), trans or cis-4,5-difluoro-1,3-dioxolan-2-one (hereinafter, both are collectively referred to as "DFEC"), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and 4-ethynyl-1,3-dioxolan-2-one (EEC). The proportion of cyclic carbonates having alkylene chains in all cyclic carbonates is preferably 55% by volume to 100% by volume, more preferably 60% by volume or more, and even more preferably 90% by volume or less.
[0069] In addition, it is preferable to use a mixture of non-aqueous solvents in order to achieve appropriate physical properties. Examples of such combinations include a combination of a cyclic carbonate and a chain ester. Suitable examples of the chain ester include one or more asymmetric chain carbonates selected from methyl ethyl carbonate (MEC), methyl propyl carbonate (MPC), methyl isopropyl carbonate (MIPC), methyl butyl carbonate, and ethyl propyl carbonate, one or more symmetric chain carbonates selected from dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, and dibutyl carbonate, pivalic acid esters such as methyl pivalate, ethyl pivalate, and propyl pivalate, and one or more chain carboxylate esters selected from methyl propionate, ethyl propionate, propyl propionate, methyl acetate, and ethyl acetate (EA). EXAMPLES
[0070] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these.
[0071] The abbreviations for compounds used in the following examples are as follows. H''-PMDA: (1R,2S,4S,5R)-cyclohexanetetracarboxylic dianhydride CBDA: 1,2,3,4-cyclobutanetetracarboxylic dianhydride PMDA: Pyromellitic dianhydride ODA: 4,4'-diaminodiphenyl ether DABAN: 4,4'-diaminobenzanilide TPE-R: 1,3-bis(4-aminophenoxy)benzene α-CD: α-cyclodextrin
[0072] <Example 1> [Preparation of polymer complex solution] In a reaction vessel equipped with a stirrer and a nitrogen inlet tube, 193.9311 g of NMP (N-methylpyrrolidone), 11.0689 g of 18-crown-6, 16.7726 g of ODA, and 4.7585 g of DABAN were added and stirred for 2 hours at 50°C under a nitrogen atmosphere. Then, 23.4689 g of H''-PMDA was added and reacted to form a polyimide precursor, thereby obtaining a polymer composite solution. In this case, the molar ratio of H''-PMDA:ODA:DABAN was 100:80:20, and the amount of 18-crown-6 was 20 mol% relative to the total of 100 mol% of the amic acid group and imide group contained in the polyimide precursor.
[0073] [TGA measurement] The obtained polymer composite solution was heated from room temperature to 500°C at a heating rate of 20°C / min using a thermogravimetric analyzer (product name "TG-DTA2000S", manufactured by Bruker AXS), and the weight was measured when the temperature reached 350°C. The remaining ratio of 18-crown-6, a cyclic molecule, when the temperature reached 350°C relative to the amount of 18-crown-6 added was calculated according to the following formula. The results are shown in Table 1. Residual rate [wt%] = ((Weight at 350°C [g]) - (Theoretical weight if all 18-crown-6 volatilizes [g])) / ((Theoretical weight if no 18-crown-6 volatilizes [g]) - (Theoretical weight if all 18-crown-6 volatilizes [g])) x 100
[0074] [IR measurement] The polymer composite solution obtained above was spin-coated on a non-alkali glass wafer and heated at 120°C, 150°C, 200°C, 250°C, and 300°C for 10 minutes each to remove the solvent and imidize the film, thereby obtaining a polymer composite film with a thickness of 10 μm. The obtained polymer composite film was then subjected to IR measurement using an IR measurement device (product name "FT / IR-4100", manufactured by JASCO Corporation). The results are shown in Figure 1.
[0075] [Mechanical strength measurement] The polymer composite solution obtained above was spin-coated on a non-alkali glass wafer and heated at 120°C, 150°C, 200°C, 250°C, and 350°C for 10 minutes each to remove the solvent and imidize the film, obtaining a polymer composite film with a thickness of 10 μm. The obtained polymer composite film was then used to measure the elastic modulus, elongation, and breaking energy using a tensile tester (product name "Tensilon (registered trademark) RTG-1350", manufactured by A&D Co., Ltd.). The results are shown in Table 2.
[0076] [Preparation of negative electrode sheet] The polymer composite solution obtained above, silicon element (Si), and acetylene black were mixed so that the weight ratio of silicon element (Si):polymer composite:acetylene black was 60:30:10 to prepare a negative electrode mixture paste. This negative electrode mixture paste was applied to one side of a nickel-plated steel foil (current collector), dried at 110°C for 1 minute, and then pressurized, heated from room temperature to 360°C at a constant rate over 1.5 hours, heated at 360°C for 1.5 hours, and then allowed to cool to remove the solvent and imidize the material. The negative electrode mixture paste was punched out to a predetermined size to produce a current collector of 10 μm and a negative electrode sheet of 20 μm in thickness.
[0077] [Battery construction] The negative electrode sheet obtained above was placed opposite metallic lithium via a glass filter (GA-100 manufactured by ADVANTEC), and a non-aqueous electrolyte was added and sealed to prepare a 2032-type coin battery. The non-aqueous electrolyte was prepared by dissolving LiPF6 as an electrolyte salt to a concentration of 1M in a non-aqueous solvent containing ethylene carbonate (EC):diethyl carbonate (DEC) = 1:1 (volume ratio) and 1% by weight of vinylene carbonate.
[0078] [Evaluation of battery characteristics] In a thermostatic chamber at 30°C, the coin-type battery prepared above was charged at a constant current of 0.1C to 0.001V, with the direction in which Li is absorbed in the negative electrode sheet being charged, and then discharged at a constant current of 0.1C to 1V, and the initial efficiency was calculated according to "initial efficiency [%] = discharge capacity [mAh] / charge capacity [mAh] × 100". Next, a cycle test was performed by repeatedly charging and discharging under the above conditions. The results of the cycle test were calculated as a ratio to the initial discharge capacity. The results are shown in Table 3. The "C" in 0.1C represents the current value when charging and discharging. For example, 1C refers to the current value at which the theoretical capacity can be fully discharged (or fully charged) in 1 / 1 hour, and 0.1C refers to the current value at which the theoretical capacity can be fully discharged (or fully charged) in 1 / 0.1 hour.
[0079] <Comparative Example 1> In a reaction vessel equipped with a stirrer and a nitrogen inlet tube, 205.0000g of NMP (N-methylpyrrolidone), 16.7726g of ODA, and 4.7585g of DABAN were charged, and the mixture was stirred at 50°C for 30 minutes under a nitrogen atmosphere. Then, 23.4689g of H''-PMDA was added and reacted to form a polyimide precursor, thereby obtaining a polyimide precursor solution. At this time, the molar ratio of H''-PMDA:ODA:DABAN was 100:80:20. Next, 11.0689g of 18-crown-6 was added to the obtained polyimide precursor solution, and the mixture was mixed at room temperature under air to obtain a mixed solution of the polyimide precursor and 18-crown-6. The amount of 18-crown-6 was 20 mol% with respect to the total of 100 mol% of the amic acid group and imide group contained in the polyimide precursor. Then, using the obtained mixed solution, TGA measurement was performed in the same manner as in Example 1 to measure the remaining rate of 18-crown-6, a cyclic molecule, when the temperature reached 350° C. The results are shown in Table 1.
[0080] <Comparative Example 2> In a reaction vessel equipped with a stirrer and a nitrogen inlet tube, 205.0000g of NMP (N-methylpyrrolidone), 16.7726g of ODA, and 4.7585g of DABAN were charged, and the mixture was stirred at 50°C for 30 minutes under a nitrogen atmosphere. Then, 23.4689g of H″-PMDA was added and reacted to form a polyimide precursor, thereby obtaining a polyimide precursor solution. At this time, the molar ratio of H″-PMDA:ODA:DABAN was 100:80:20. Then, using the obtained polyimide precursor solution, IR measurement, mechanical strength measurement, and evaluation of battery characteristics were performed in the same manner as in Example 1. The results are shown in FIG. 1 and Tables 2 and 3.
[0081] <Example 2> In a reaction vessel equipped with a stirrer and a nitrogen inlet tube, 206.2725 g of NMP (N-methylpyrrolidone), 8.7275 g of 18-crown-6, 7.2400 g of TPE-R, and 11.5716 g of ODA were charged, and the mixture was stirred for 2 hours at 50° C. under a nitrogen atmosphere, and then 16.1883 g of CBDA was added and reacted to form a polyimide precursor, thereby obtaining a polymer composite solution. At this time, the molar ratio of CBDA:TPE-R:ODA was 100:30:70, and the amount of 18-crown-6 was 20 mol % relative to the total of 100 mol % of the amic acid group and imide group contained in the polyimide precursor. Then, using the obtained polymer composite solution, TGA measurement was performed in the same manner as in Example 1, and the residual ratio of 18-crown-6, which is a cyclic molecule, at 350° C. was measured. In addition, IR measurement, mechanical strength measurement, and evaluation of battery properties were performed in the same manner as in Example 1. The results are shown in Table 1, Figure 2, and Tables 2 and 3.
[0082] <Comparative Example 3> In a reaction vessel equipped with a stirrer and a nitrogen inlet tube, 215.0000g of NMP (N-methylpyrrolidone), 7.2400g of TPE-R, and 11.5716g of ODA were charged, and the mixture was stirred at 50°C for 30 minutes under a nitrogen atmosphere, after which 16.1883g of CBDA was added and reacted to form a polyimide precursor, thereby obtaining a polyimide precursor solution. At this time, the molar ratio of CBDA:TPE-R:ODA was 100:30:70. Next, 8.7275g of 18-crown-6 was added to the obtained polyimide precursor solution, and the mixture was mixed at room temperature under air to obtain a mixed solution of the polyimide precursor and 18-crown-6. The amount of 18-crown-6 was 20 mol% relative to the total of 100 mol% of the amic acid group and imide group contained in the polyimide precursor. Then, using the obtained mixed solution, TGA measurement was performed in the same manner as in Example 1 to measure the remaining rate of 18-crown-6, a cyclic molecule, when the temperature reached 350° C. The results are shown in Table 1. In Comparative Example 3, the polyimide precursor solution (solution before adding 18-crown-6), silicon element (Si), and acetylene black were mixed so that the ratio of silicon element (Si):polyimide precursor:acetylene black was 60:30:10 (weight ratio), and then 18-crown-6 was added and mixed at room temperature under air to obtain a negative electrode mixture paste. The amount of 18-crown-6 was 20 mol% relative to the total of 100 mol% of the amic acid group and imide group contained in the polyimide precursor. Then, the battery characteristics were evaluated using the obtained negative electrode mixture paste in the same manner as in Example 1. The results are shown in Table 3. The obtained negative electrode mixture paste was used to perform TGA measurement in the same manner as in Example 1, and the residual ratio of 18-crown-6, which is a cyclic molecule, at 360°C was measured, and was 8.79% by weight.
[0083] <Comparative Example 4> In a reaction vessel equipped with a stirrer and a nitrogen inlet tube, 215.0000g of NMP (N-methylpyrrolidone), 7.2400g of TPE-R, and 11.5716g of ODA were charged, and the mixture was stirred at 50°C for 30 minutes under a nitrogen atmosphere, after which 16.1883g of CBDA was added and reacted to form a polyimide precursor, thereby obtaining a polyimide precursor solution. At this time, the molar ratio of CBDA:TPE-R:ODA was 100:30:70. Using the obtained polyimide precursor solution, IR measurement, mechanical strength measurement, and evaluation of battery characteristics were performed in the same manner as in Example 1. The results are shown in FIG. 2 and Tables 2 and 3.
[0084] <Example 3> 215.0000g of NMP (N-methylpyrrolidone), 8.8448g of 18-crown-6, and 16.7530g of ODA were put into a reaction vessel equipped with a stirrer and a nitrogen inlet tube, and the mixture was stirred for 2 hours at 50°C under a nitrogen atmosphere, after which 18.2470g of PMDA was added and reacted to form a polyimide precursor, thereby obtaining a polymer composite solution. At this time, PMDA:ODA (molar ratio) = 100:100, and the amount of 18-crown-6 was 20 mol% relative to the total of 100 mol% of the amic acid group and imide group contained in the polyimide precursor. Then, using the obtained polymer composite solution, TGA measurement was performed in the same manner as in Example 1, and the residual rate of 18-crown-6, which is a cyclic molecule, at 350°C was measured. In addition, mechanical strength measurement and evaluation of battery characteristics were performed in the same manner as in Example 1. The results are shown in Tables 1, 2, and 3. In Example 3, when producing the negative electrode sheet, the ratio of silicon (Si):polymer composite:acetylene black was 60:25:15 (weight ratio), and in the cycle test for evaluating the battery characteristics, the first and second cycles were charged and discharged at 0.1C, and from the third cycle onwards, the charge and discharge were both at 0.5C.
[0085] <Comparative Example 5> In a reaction vessel equipped with a stirrer and a nitrogen inlet tube, 215.0000g of NMP (N-methylpyrrolidone) and 16.7530g of ODA were charged, and the mixture was stirred at 50°C for 30 minutes under a nitrogen atmosphere, after which 18.2470g of PMDA was added and reacted to form a polyimide precursor, thereby obtaining a polyimide precursor solution. At this time, PMDA:ODA (molar ratio) = 100:100. Next, 8.8448g of 18-crown-6 was added to the obtained polyimide precursor solution, and the mixture was mixed at room temperature under air to obtain a mixed solution of polyimide precursor and 18-crown-6. The amount of 18-crown-6 was 20 mol% relative to the total of 100 mol% of the amic acid group and imide group contained in the polyimide precursor. Then, using the obtained mixed solution, TGA measurement was performed in the same manner as in Example 1, and the residual ratio of 18-crown-6, which is a cyclic molecule, at 350°C was measured. The results are shown in Table 1.
[0086] <Comparative Example 6> In a reaction vessel equipped with a stirrer and a nitrogen inlet tube, 215.0000g of NMP (N-methylpyrrolidone) and 16.7530g of ODA were put in, and the mixture was stirred at 50°C for 30 minutes under a nitrogen atmosphere, after which 18.2470g of PMDA was added and reacted to form a polyimide precursor, thereby obtaining a polyimide precursor solution. At this time, the PMDA:ODA (molar ratio) was 100:100. Then, using the obtained polyimide precursor solution, mechanical strength measurements and evaluation of battery characteristics were performed in the same manner as in Example 1. The results are shown in Tables 2 and 3. In Comparative Example 6, similar to Example 3, when producing the negative electrode sheet, the ratio of silicon element (Si):polymer composite:acetylene black was 60:25:15 (weight ratio), and the cycle test in the evaluation of battery characteristics was performed at 0.1C for both charge and discharge in the first and second cycles, and at 0.5C from the third cycle onwards.
[0087] <Example 4> In a reaction vessel equipped with a stirrer and a nitrogen inlet tube, 187.4648 g of NMP (N-methylpyrrolidone), 12.5352 g of 18-crown-6, and 23.7610 g of ODA were charged, and the mixture was stirred for 2 hours at 50° C. under a nitrogen atmosphere, and then 13.2990 g of H″-PMDA and 12.9400 g of PMDA were added and reacted to form a polyimide precursor, thereby obtaining a polymer composite solution. At this time, the molar ratio of H″-PMDA:PMDA:ODA was 50:50:100, and the amount of 18-crown-6 was 20 mol % relative to the total of 100 mol % of the amic acid group and imide group contained in the polyimide precursor. Then, using the obtained polymer composite solution, TGA measurement was performed in the same manner as in Example 1, and the residual ratio of 18-crown-6, which is a cyclic molecule, at 350° C. was measured. In addition, mechanical strength measurement and evaluation of battery properties were performed in the same manner as in Example 1. The results are shown in Tables 1, 2, and 3.
[0088] <Comparative Example 7> In a reaction vessel equipped with a stirrer and a nitrogen inlet tube, 200.0000g of NMP (N-methylpyrrolidone) and 23.7610g of ODA were charged, and the mixture was stirred at 50°C for 0.5 hours under a nitrogen atmosphere. Then, 13.2990g of H″-PMDA and 12.9400g of PMDA were added and reacted to form a polyimide precursor, thereby obtaining a polyimide precursor solution. At this time, the molar ratio of H″-PMDA:PMDA:ODA was 50:50:100. Then, using the obtained polyimide precursor solution, mechanical strength measurements and evaluation of battery characteristics were performed in the same manner as in Example 1. The results are shown in Tables 2 and 3.
[0089] <Example 5> In a reaction vessel equipped with a stirrer and a nitrogen inlet tube, 198.9388 g of NMP (N-methylpyrrolidone), 16.0612 g of α-CD, 7.2400 g of TPE-R, and 11.5716 g of ODA were charged, and the mixture was stirred for 2 hours at 50° C. under a nitrogen atmosphere, after which 16.1883 g of CBDA was added and reacted to form a polyimide precursor, thereby obtaining a polymer composite solution. At this time, the molar ratio of CBDA:TPE-R:ODA was 100:30:70, and the amount of α-CD was 10 mol % relative to the total of 100 mol % of the amide acid group and imide group contained in the polyimide precursor. Then, using the obtained polymer composite solution, TGA measurement was performed in the same manner as in Example 1. Also, the battery characteristics were evaluated in the same manner as in Example 1. The results are shown in Tables 1 and 3.
[0090] In Example 5, the TGA measurement was performed at 350°C to determine the amount of remaining α-CD, as in the case of using 18-crown-6 as a cyclic molecule. On the other hand, when the TGA measurement was performed up to 600°C with α-CD alone, about 10% by weight of non-volatilized carbonized components were present. In Example 5, the TGA measurement at 350°C is estimated to be about 10% by weight lower than the measured results shown in Table 1. In addition, regarding the evaluation of battery characteristics, in Example 5, when the negative electrode sheet was manufactured, silicon oxide: polymer composite: acetylene black = 80: 15: 5 (weight ratio), and in the cycle test, the discharge voltage was 1.5V.
[0091] <Comparative Example 8> In a reaction vessel equipped with a stirrer and a nitrogen inlet tube, 215.0000g of NMP (N-methylpyrrolidone), 7.2400g of TPE-R, and 11.5716g of ODA were charged, and the mixture was stirred at 50°C for 0.5 hours under a nitrogen atmosphere, and then 16.1883g of CBDA was added and reacted to form a polyimide precursor, thereby obtaining a polyimide precursor solution. At this time, the molar ratio of CBDA:TPE-R:ODA was 100:30:70. Next, the obtained polyimide precursor solution, silicon oxide, and acetylene black were mixed so that the ratio of silicon oxide:polyimide precursor:acetylene black was 80:15:5 (weight ratio), and then α-CD was added and mixed at room temperature under air to obtain a negative electrode mixture paste. The amount of α-CD was 10 mol% with respect to the total of 100 mol% of the amic acid group and imide group contained in the polyimide precursor. Then, using the obtained negative electrode mixture paste, the battery characteristics were evaluated in the same manner as in Example 1. The results are shown in Table 3. In Comparative Example 8, the discharge voltage was set to 1.5 V in the cycle test for evaluating the battery characteristics.
[0092] <Comparative Example 9> Into a reaction vessel equipped with a stirrer and a nitrogen inlet tube, 215.0000 g of NMP (N-methylpyrrolidone), 7.2400 g of TPE-R, and 11.5716 g of ODA were charged, and after stirring at 50 °C for 0.5 h under a nitrogen atmosphere, 16.1883 g of CBDA was added and reacted to form a polyimide precursor, thereby obtaining a polyimide precursor solution. At this time, CBDA:TPE-R:ODA (molar ratio) = 100:30:70. Then, using the obtained polyimide precursor solution, the battery characteristics were evaluated in the same manner as in Example 1. The results are shown in Table 3. In Comparative Example 8, when manufacturing the negative electrode sheet, silicon oxide:polymer composite:acetylene black = 80:15:5 (weight ratio), and for the cycle test in the evaluation of the battery characteristics, the discharge voltage was set to 1.5 V.
[0093]
Table 1
[0094]
Table 2
[0095]
Table 3
[0096] <Evaluation of TGA measurement> As is clear from the results in Table 1, in Examples 1 to 5 in which the tetracarboxylic acid component and the diamine component were reacted in the presence of 18-crown-6 as a cyclic molecule to form a polyimide precursor, even when heated to 350 °C, a considerable amount of 18-crown-6 (boiling point: 190 °C) or α-CD remained, and at least a part of the polyimide precursor or polyimide and 18-crown-6 or α-CD as a cyclic molecule was complexed to form a polymer composite. On the other hand, in Comparative Examples 1, 3, and 5 in which 18-crown-6 as a cyclic molecule was mixed with the polyimide precursor, when heated to 350 °C, almost no 18-crown-6 remained, indicating that the polyimide precursor and 18-crown-6 as a cyclic molecule did not form a complex. As described above, when 18-crown-6 as a cyclic molecule was mixed with the polyimide precursor as in Comparative Examples 1, 3, and 5, and the imidization reaction was carried out at a temperature of 300 to 350 °C, almost no 18-crown-6 as a cyclic molecule remained. Therefore, for the measurement of mechanical strength and battery characteristics, as appropriate, evaluation was carried out in the state of the polyimide precursor solution without mixing 18-crown-6 as a cyclic molecule, as in Comparative Examples 2, 4, 6, and 7. That is, as in Comparative Examples 1, 3, and 5 described above, even if 18-crown-6 as a cyclic molecule was mixed with the polyimide precursor, it was considered that the same results would be obtained whether or not 18-crown-6 as a cyclic molecule was mixed. Therefore, evaluation was carried out in the state of the polyimide precursor solution without mixing 18-crown-6 as a cyclic molecule, as in Comparative Examples 2, 4, 6, and 7.
[0097] <Evaluation of IR measurement> Figure 1 shows the IR spectra of Example 1 and Comparative Example 2 (Figure 1(A) is the spectrum at 750 - 800 cm -1 and Figure 1(B) is the spectrum at 1680 - 1730 cm -1 ), and Figure 2 shows the IR spectra of Example 2 and Comparative Example 4 (Figure 2(A) is the spectrum at 770 - 820 cm -1 and Figure 2(B) is the spectrum at 1680 - 1730 cm -1 ). As is clear from Figures 1 and 2, at least a part of the polyimide precursor or polyimide and 18-crown-6 as a cyclic molecule was complexed, and a peak shift characteristic of the polyimide precursor and polyimide was observed.
[0098] <Evaluation of mechanical strength measurement> As is clear from the results in Table 2, in Examples 1 to 4, at least a portion of the polyimide precursor or polyimide and 18-crown-6 as a cyclic molecule were complexed to form a polymer composite, resulting in an increase in the breaking energy.
[0099] <Evaluation of battery characteristics> As is clear from the results in Table 3, in Examples 1 to 5, the polyimide precursor or polyimide and 18-crown-6 or α-CD as the cyclic molecule were at least partially complexed to form a polymer composite, which resulted in achieving superior charge-discharge cycle characteristics compared to the case where a polymer composite was not formed. On the other hand, Comparative Examples 3 and 8, in which 18-crown-6 or α-CD was mixed as a cyclic molecule with the polyimide precursor, showed inferior charge-discharge cycle characteristics compared to Comparative Examples 4 and 9, in which no cyclic molecule was mixed. From these results, it can be said that in Comparative Example 8, in which α-CD was mixed, the cyclic molecule was not complexed, similar to Comparative Example 3, in which 18-crown-6 was mixed as a cyclic molecule. [Industrial Applicability]
[0100] The binder for an electricity storage device of the present invention is suitably used in the production of an electricity storage device.
Claims
1. A binder for an electricity storage device contains a polymer composite obtained by combining a polyimide precursor containing a reaction product of a tetracarboxylic acid component and a diamine component and / or a polyimide obtained by imidizing a part or all of the polyimide precursor with a cyclic molecule having a plurality of ether bonds, the cyclic molecule is at least one selected from cyclodextrin, crown ether, and thiocrown ether; A binder for an electricity storage device, wherein, when the binder is heated from room temperature to 500°C at a heating rate of 20°C / min using a thermogravimetric measuring device and the weight when the temperature reaches 350°C is measured, the residual rate of cyclic molecules in the binder for an electricity storage device, as represented by the following formula, is 10% by weight or more (however, when there is a component that will be carbonized without being complexed, the proportion of the component that will be carbonized when the cyclic molecule is heated alone is determined in advance, and the value obtained by subtracting the amount of the component that will be carbonized is used as the residual rate). Residual rate of cyclic molecules [wt %]=((weight [g] at 350° C.)−(theoretical value of weight when all cyclic molecules are volatilized [g])) / ((theoretical value of weight when no cyclic molecules are volatilized [g])−(theoretical value of weight when all cyclic molecules are volatilized [g]))×100
2. 2. The binder for an electricity storage device according to claim 1, wherein a content ratio of the cyclic molecules in the binder is 4 mol % or more and 25 mol % or less with respect to 100 mol % in total of an amic acid group and an imide group contained in the polyimide precursor and / or a polyimide obtained by imidizing a part or all of the polyimide precursor.
3. 3. The binder for an electrical storage device according to claim 1, wherein a proportion of the alicyclic tetracarboxylic dianhydride in 100 mol % of the tetracarboxylic acid component is 35 mol % or more.
4. 3. The binder for an electricity storage device according to claim 1, wherein the polymer composite is obtained by reacting the tetracarboxylic acid component with the diamine component in the presence of the cyclic molecule.
5. A varnish comprising the binder for an electricity storage device according to claim 1 or 2.
6. An electrode for an electricity storage device, comprising the binder for an electricity storage device according to claim 1 or 2 and an active material.
7. The electrode for an electricity storage device according to claim 6 , wherein the active material is a silicon-containing negative electrode active material.
8. An electricity storage device comprising the electrode according to claim 6.
9. A method for producing the binder for an electrical storage device according to claim 1 or 2, comprising the steps of: A method for producing a binder for an electrical storage device, comprising the step of reacting a tetracarboxylic acid component with a diamine component in the presence of a cyclic molecule having a plurality of ether bonds to obtain a polyimide precursor.
Citation Information
Patent Citations
Polyimide binder and negative plate
CN113555552A
Coating film composition, method for producing coating film and electronic part using the same
JP2005008730A
Method for producing composite polymer, and composite polymer composition
JP2007046013A
Polyimide resin composition
JP2008120869A
Binder for lithium ion battery electrode, paste for lithium ion battery negative electrode using the same and manufacturing method of lithium ion battery negative electrode
JP2013089437A